2019
DOI: 10.23986/afsci.78169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycorrhiza on yield and quality of lettuce grown on medium with different levels of phosphorus and selenium

Abstract: Lettuce plants were grown in the foil tunnel in pots filled with peat substrate. The experimental factors were: concentration of phosphorus in the substrate (70 or 140 mg dm-3), inoculation of substrate with arbuscular mycorrhizal fungi (+AMF or –AMF) and concentration of selenium in the substrate (0, 6 or 12 mg dm-3). Mycorrhizal frequency in roots was affected by concentration of P, inoculation with AMF and interaction between these factors. Higher mycorrhizal frequency was found in plants inoculated with AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Some previous reports also indicated that mycorrhizal colonization can improve the P status of plants (Chen et al, 2010;Goicoechea et al, 2014;He et al, 2017c). The result that mycorrhizal colonization rate was the highest in P20 treatment in the present study did not agree with the conclusions of some studies, which have shown a negative correlation between AMF colonization rate and soil available P (Asghari et al, 2005;Kowalska and Konieczny, 2019). It might be due to the relatively low levels of available P in the soil in all treatments (<10 mg available P kg -1 soil).…”
Section: Discussioncontrasting
confidence: 99%
“…Some previous reports also indicated that mycorrhizal colonization can improve the P status of plants (Chen et al, 2010;Goicoechea et al, 2014;He et al, 2017c). The result that mycorrhizal colonization rate was the highest in P20 treatment in the present study did not agree with the conclusions of some studies, which have shown a negative correlation between AMF colonization rate and soil available P (Asghari et al, 2005;Kowalska and Konieczny, 2019). It might be due to the relatively low levels of available P in the soil in all treatments (<10 mg available P kg -1 soil).…”
Section: Discussioncontrasting
confidence: 99%
“…In previous investigations, the increased efficiency of Se biofortification under AMF inoculation has been documented in several plants, such as Allium species [ 25 ], wheat [ 50 ], and soybean [ 51 ]. Legumes have been reported to positively react to the AMF application in terms on Se accumulation, contrary to lettuce, maize, alfalfa, and forage grass ( Urochloa decumbens ) [ 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…G. fasciculatum or a commercial preparation of G. intraradices and G. mosseae were also able to increase the mineral content and growth of lettuce [ 47 , 48 ]. R. intraradices inoculated in plants under low P concentration improved yield but did not affect Se concentration [ 49 ], while R. intraradices -based commercial preparation, especially when supplied together with a legume-derived protein hydrolysate (PH), improved lettuce’s fresh marketable yield, dry weight, P, K and Fe via an increase in total root length and surface [ 50 ]. AMF commercial inocula and/or F. mosseae increased plant growth and macro- and micronutrient use efficiency in cucumber [ 51 ].…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 99%